Hybrid response to SARS-CoV-2 and Neisseria meningitidis C after an OMV-adjuvanted immunization in mice and their offspring - Amanda Izeli Portilho; Hernan Hermes Monteiro da Costa; Marcia Grando Guereschi; Carlos Roberto Prudencio; Elizabeth De Gaspari (Human Vaccines & Immunotherapeutics)
COVID-19, caused by SARS-CoV-2, and meningococcal disease, caused by Neisseria meningitidis, are relevant infectious diseases, preventable through vaccination. Outer membrane vesicles (OMVs), released from Gram-negative bacteria, such as N. meningitidis, present adjuvant characteristics and may confer protection against meningococcal disease. Here, we evaluated in mice the humoral and cellular immune response to different doses of receptor binding domain (RBD) of SARS-CoV-2 adjuvanted by N. meningitidis C:2a:P1.5 OMVs and aluminum hydroxide, as a combined preparation for these pathogens. The immunization induced IgG antibodies of high avidity for RBD and OMVs, besides IgG that recognized the Omicron BA.2 variant of SARS-CoV-2 with intermediary avidity. Cellular immunity showed IFN-γ and IL-4 secretion in response to RBD and OMV stimuli, demonstrating immunologic memory and a mixed Th1/Th2 response. Offspring presented transferred IgG of similar levels and avidity as their mothers. Humoral immunity did not point to the superiority of any RBD dose, but the group immunized with a lower antigenic dose (0.5 μg) had the better cellular response. Overall, OMVs enhanced RBD immunogenicity and conferred an immune response directed to N. meningitidis too.